2012
DOI: 10.1111/ajco.12047
|View full text |Cite
|
Sign up to set email alerts
|

Australian general practitioners' preferences for managing the care of people diagnosed with cancer

Abstract: While many GPs are currently involved in some aspects of cancer management, with training, good communication and support from specialists this role may be successfully expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…56,58,60,62,69,70 PCPs reported that they rarely or inconsistently received sufficient correspondence from oncologists. 43,48,52,58,60,67 Though oncologists' letters contained details on investigation and examination findings, items such as treatment/management plans, future management and expectations, goals and procedures of follow-up, and psychosocial concerns were less commonly mentioned. 56,62 In one study, approximately half of PCPs reported never having received a treatment summary.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
See 3 more Smart Citations
“…56,58,60,62,69,70 PCPs reported that they rarely or inconsistently received sufficient correspondence from oncologists. 43,48,52,58,60,67 Though oncologists' letters contained details on investigation and examination findings, items such as treatment/management plans, future management and expectations, goals and procedures of follow-up, and psychosocial concerns were less commonly mentioned. 56,62 In one study, approximately half of PCPs reported never having received a treatment summary.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
“…52 In terms of information preferences, 85-99 % of PCPs would have liked to have received additional information from oncologists regarding cancer treatments, 40,56,57 the referring PCP's role, 56 findings of investigations and likely prognosis, 56 the oncologist's follow-up plan, 56,57 clinical practice guidelines for survivorship care, 40 and potential short and long term sideeffects, including suggested management.…”
Section: Information Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is little systematic attention to developing models of care that increase the role of primary care providers. There is also some evidence that Australian cancer specialists prefer controlling follow-up locally 6 and general practitioners (GPs) may be reluctant to take on follow-up and other cancer care roles 7 without improved training and supportive models of care.…”
Section: The Imperative For Changementioning
confidence: 99%